Performance Characterization of Novel Dual Stator Sandwiched Rotor Hybrid Magnetic Pole Six-Phase PMSG for Harnessing Wind Power - Kumar R.R.; Paul R.; Sarma J.; Kumari A.; Chetri C.; Saket R.K.; Padmanaban S.; Leonowicz Z. (My University, 2025)
Head objective of the paper is to create and stimulate a Novel Dual Stator Sandwiched Rotor Hybrid Magnetic Pole Six-Phase PMSG (NDSSRHMPSP-PMSG) for harnessing wind power. Wind energy is the most optimized plan for innovation since it erases the need of water and is ecoaccommodating and can be a superior option for expanded energy usage. A multiphase PMSG is a superior alternative for wind energy utilization. The two-fold rotor-stator setup upgrades the machine's voltage regulation as well as its dependability and execution. The designed NDSSRHMPSP-PMSG possesses novelty in terms of its magnet structure. A Hybrid Magnetic Pole (HMP) is inserted into the rotatory portions. The concept of HMP introduces the combination of V-Shaped Magnets (VSM) and Multi-Layer Embedded Magnets (MLEM). This remarkable combination of two different magnetic formation provides a higher flux density and contributes towards an efficient operation of the proposed system. To construct the generator optimally and for evaluation, magnetostatic and transient setups are used. Because of proper examination, it may be very well presumed that the proposed novel framework is legitimate and effective. © 2021 IEEE